PEDAGOGICAL PROBLEMS IN DEVELOPING STUDENTS' LEARNING ACTIVITIES AND THEIR EXPLANATION - Ruziyeva Nigora Kamtarovna (Bright Mind Publishing, 2025)
This article briefly describes the differences between academic and cognitive activities, problems that arise in the development of students' cognitive activities, measures to eliminate them, and the work of scientists on these problems.
Keywords: Educational process, innovative technology, problem situation, independent thinking, creative thinking.